The peculiarities of sorghum seed-growing in the Rostov region - S. I. Gorpinichenko; N. A. Kovtunova; E. A. Shishova; G. M. Ermolina; A. E. Romanyukin (Зерновое хозяйство России)
The peculiarities of sorghum seed-growing in the Rostov region To obtain high-qualitative seeds it’s necessary to improve seed-growing and to follow all recommendations concerning cultivation technology, harvesting, after-harvesting seed processing and their storage. Thus, the study of the peculiarities of sorghum seed-growing is of great importance today. The system of sorghum seed-growing includes following stages: to develop varieties and hybrids; to grow basic seeds, sterile lines, fixers of sterility, restorers of fertility, hybrids; to supply farms with basic seeds for further reproduction and sale. The seeding work with the sorghum varieties registered in the State List of breeding achievements of RF is carried out in three-staged scheme: farm of selection, seeding farm (pre-basic seeds) and basic seeds. Maintenance of high varietal purity is carried out using mass, individual-family and negative selection. At present 16 varieties and hybrids developed by the FSBSI “Agricultural Research Center “Donskoy” are introduced into the State List of breeding achievements of RF in the Rostov region. The varieties of Sudan grass “Aleksandrina” and “Anastasiya”, the varieties of sweet sorghum “Debyut” and “Listvenit”, the varieties of grain sorghum “Zernogradskoe 88”, “Velikan”, “Orlovskoe”, “Luchistoe”, “Khazine 28” are of wide use in the agriculture.